2017
DOI: 10.1590/0103-6440201601524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Bioactive Glass Ceramic on the Control of Enamel and Dentin Erosion Lesions

Abstract: This study evaluated the effect of a bioactive glass ceramic for the control of erosion and caries lesions. Fragments (n=10) of bovine enamel and root dentin received daily application of different treatments (Biosilicate; Acidulated Phosphate Fluoride-APF; Untreated -control) during the performance of erosive cycles. Surfaces were analyzed with 3D optical profilometry to quantify the superficial loss in four periods (1, 7, 14 and 21 days), as well as the lesion depth with confocal laser scanning microscopy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
0
24
0
11
Order By: Relevance
“…Surface microhardness of the enamel tissue decreased after the demineralization procedure and increased after application of bioactive glass. The value of microhardness was found to be higher in bioactive glass group when compared to the control group or application of other agents [19][20][21]23,29,38]. A study reported the recovery rate of microhardness on demineralized enamel surface after treatment with bioactive glass was 28.8% [21].…”
Section: Zhang Et Al (2019) [37]mentioning
confidence: 99%
“…Surface microhardness of the enamel tissue decreased after the demineralization procedure and increased after application of bioactive glass. The value of microhardness was found to be higher in bioactive glass group when compared to the control group or application of other agents [19][20][21]23,29,38]. A study reported the recovery rate of microhardness on demineralized enamel surface after treatment with bioactive glass was 28.8% [21].…”
Section: Zhang Et Al (2019) [37]mentioning
confidence: 99%
“…The application of biosilicate microparticles on dentin induces the deposition of carbonated hydroxyapatite, which leads to the formation of a mineralized surface layer [12,13]. This layer adhering to dentin constantly releases calcium and phosphate ions that are present in the composition of microparticles, becoming possible adjuvant factors for tooth remineralization [14,15,16]. Moreover, a previous study [18] suggested that blasting with bioactive glasses could increase the durability of dentin bonds, could induce dentin remineralization, and could enhance its repair capacity.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Biosilicate paste: a 10% biosilicate paste was prepared immediately before application by adding 1 mL of distilled and deionized water in microtubes containing 0.1 g of biosilicate powder. The paste was first scrubbed onto the dentin surface for 30 seconds using a microbrush and, then, it remained still for five minutes [14]. Afterwards, the material was carefully removed with absorbent paper.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse contexto, biomateriais como o Biosilicato ® tornam-se atraentes para esse fim, pois são capazes de promover a remineralização de tecidos ósseos por meio da formação de uma camada de hidroxiapatita carbonatada (Crovace, Souza, Chinaglia, Peitl, & Zanotto, 2016). Além disso, estudos recentes evidenciam seu uso bem sucedido em testes in vitro para o tratamento de erosão dental (Chinelatti et al, 2017) e em testes clínicos para tratamento de hipersensibilidade dentinária (Tirapelli et al, 2011) e de cárie (Pintado-Palomino, de Almeida, da Motta, Fortes, & Tirapelli, 2019).…”
Section: Introductionunclassified